A2A ADENOSINE RECEPTORS REGULATE MULTIPLE ORGAN FAILURE AFTER HEMORRHAGIC SHOCK IN MICE. Issue 4 (26th October 2022) - Kelestemur, Taha; Németh, Zoltán H.; Pacher, Pal; Antonioli, Luca; Haskó, György
ABSTRACT: Trauma hemorrhagic shock (T/HS) is a clinical condition that causes multiple organ failure that needs rapid intervention. Restricted oxygen at the cellular level causes inflammation and subsequent cell death. Adenosine triphosphate is the universal intracellular energy currency and an important extracellular inflammatory signaling molecule. Adenosine, an endogenous nucleotide formed as a result of the breakdown of adenosine triphosphate, is also released during T/HS. Adenosine binds to four G protein–coupled receptors (A1R, A2a, A2b, A3R ) called adenosine receptors or P1 receptors. In the present study, we evaluated the effect of activation, inactivation, and genetic absence of A2aR (A2aR −/− mice) on T/HS-induced multiple organ failure. Wild-type mice were pretreated (30 min before shock induction) with an agonist or antagonist and then subjected to T/HS by withdrawing arterial blood and maintaining the blood pressure between 28 and 32 mm Hg. A2aR −/− mice were subjected to T/HS in the absence of pharmacologic treatment. Neutrophil sequestration was assessed by detecting myeloperoxidase, and Evans blue dye (EBD) method was used to analyze lung permeability. Blood and lung inflammatory cytokine levels were determined by sandwich enzyme-linked immunosorbent assay. The liver enzymes aspartate aminotransferase and alanine aminotransferase were determined spectrophotometrically from plasma. Activation of the apoptotic cascade was evaluated using a mouse apoptosis array. Our results demonstrate that the selective A2aR agonist CGS21680 decreases lung neutrophil sequestration, lung proinflammatory cytokines IL-6 and TNF-α, and bronchoalveolar lavage EBD. Pretreatment with the selective antagonist ZM241385 and genetic blockade in A2aR −/− mice increased neutrophil sequestration, proinflammatory cytokine levels, and bronchoalveolar lavage fluid EBD. The myeloperoxidase level in the lung was also increased in A2aR −/− mice. We observed that antiapoptotic markers decreased significantly with the absence of A2aR in the lung and spleen after T/HS. In conclusion, our data demonstrate that activation of A2aR regulates organ injury and apoptosis in the setting of T/HS.